Students’ and Lecturers’ Perspectives on The Factors Influencing One’s Metaphor Competence - Dewi, Ienneke Indra (Humaniora, 2013)
This article aimed to see the perspective of lecturers and students regarding the factors influencing people?s metaphor competence in daily life. Twenty-one students were interviewed and ten lecturers were sent a questionnaire asking about the factors that might influence the use of metaphors. The results show that both lecturers and students agree that language mastery is not the only one which determines the ability of people in comprehending and producing metaphors. Other non-linguistic factors such as habits, environment, personality, social network, logical thinking and general knowledge also influence people. The respondents propose that metaphors are to be taught to students not only in language subjects but also in other subjects such as Character Building or other social subjects.